Some noteworthy photosynthetic euglenophytes from Los Baños, Laguna (Philippines) and its vicinities - Arguelles, Eldrin DLR.; Martinez-Goss, Milagros R.; Shin, Woongghi (2014)
Thirty-two species of photosynthetic euglenoids belonging to the genera euglena (eight), Phacus (nine), Lepocinclis (seven), Trachelomonas (four), and one each in Euglenaformis Monomorphina, Cryptoglena and Strombomonas are identified and collected from twenty-seven sampling sites in Laguna and its vicinities. Of these taxa, sixteen species are recorded for first time in the Philippines. Diagnostic descriptions, photographs, and habitat records are given for each taxon. Keys are presented to distinguish the eight genera in the Euglenophyceae, followed by keys to the species of each genus.